Methylation analysis of tumor suppressor genes in endometroid carcinoma of endometrium using MS-MLPA - Dvořáková, Eva; Chmelařová, Marcela; Laco, Jan; Palička, Vladimír; Špaček, Jiří (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2013)
BACKGROUND: Epigenetic changes are considered to be a frequent event during tumor development. Hypermethylation of promoter CpG islands represents an alternative mechanism for inactivation of tumor suppressor genes, DNA repair genes, cell cycle regulators and transcription factors. The aim of this study was to investigate promoter methylation of specific genes in endometrial cancer by comparison with normal endometrial tissue. MATERIALS AND METHODS: We used MS-MLPA (Methylation-specific Multiplex ligation-dependent probe amplification) to compare the methylation status of 59 tissue samples of endometroid type of endometrial carcinoma with 20 control samples of non-neoplastic endometrium. RESULTS: Using 15% cut-off for methylation, we observed significantly higher methylation in the CDH13 gene in endometrial cancer group. We observed significantly higher methylation in both WT1 and GATA5 genes in IB stage of endometroid carcinoma. We also observed significantly higher methylation in GATA5 gene in the group of poorly differentiated endometroid carcinoma. CONCLUSION: The findings suggest the importance of hypermethylation of CDH13, WT1 and GATA5 genes in endometrial carcinogenesis and could have implications for future diagnostic and therapeutic strategies of endometrial cancer based on epigenetic changes.
Keywords: DNA Methylation; metylace DNA; Multiplex Polymerase Chain Reaction; Genes, Tumor Suppressor; Adult; Aged; dospělí; senioři; Endometrial Neoplasms; multiplexová polymerázová řetězová reakce; senioři nad 80 let; lidé; Carcinoma; ženské pohlaví; Humans; karcinom; Aged, 80 and over; Female; tumor supresorové geny; lidé středního věku; nádory endometria; Middle Aged